Spontaneous Resolution of Coronary Artery Pseudoaneurysm Consequent to Percutaneous Intervention with Paclitaxel-Eluting Stent - Chen, David (Texas Heart Institute, 2008)
Pseudoaneurysm formation is a rarely reported phenomenon after percutaneous coronary intervention. The natural course and clinical complications of coronary pseudoaneurysms are not well described, and the possible contribution of drug-eluting stents to the formation of coronary artery pseudoaneurysms is ill defined. Herein, we describe the case of a patient who experienced pseudoaneurysm formation 1 month after deployment of a paclitaxel-eluting stent. Healing was delayed, and there was resolution after 2 years of follow-up.